1993
DOI: 10.1063/1.355184
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of an EL5-like defect in metalorganic vapor-phase epitaxial GaAs:Sb

Abstract: An EL5-like trap in metalorganic vapor-phase epitaxially grown GaAs:Sb has been detected by deep-level transient spectroscopy. The trap behavior has been investigated by changing the growth conditions—the V/III ratio and the level of isoelectronic doping with Sb. It has been found that the activation energy of the EL5-like trap changes from Ec−0.43 eV in the undoped GaAs to Ec−0.35 eV in highly Sb-doped GaAs. It has been observed that the EL5 trap concentration increases with increasing the [AsH3] partial pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Similarly, when V R = −0.25 V and V P = 0 V is used for same sample (see Fig. 7(d)), only one shallow hole trap is observed (H 21(311)B ) at [33,[42][43][44][45][46]. It can be seen in Fig.…”
Section: Dlts and Laplace Dlts (Ldlts)mentioning
confidence: 66%
“…Similarly, when V R = −0.25 V and V P = 0 V is used for same sample (see Fig. 7(d)), only one shallow hole trap is observed (H 21(311)B ) at [33,[42][43][44][45][46]. It can be seen in Fig.…”
Section: Dlts and Laplace Dlts (Ldlts)mentioning
confidence: 66%
“…2͒ that is often observed in bulk GaAs 42 and less frequently in MOVPE GaAs. 43 Origin of the EL5 level is not fully established, nevertheless it is frequently accepted that it is a complex point defect involving gallium vacancy (V Ga ) together with, e.g., Si Ga 44 or As i . 43 It is also known that high Si doping leads to a generation of gallium vacancies or V Ga -related complexes.…”
Section: Resultsmentioning
confidence: 99%
“…43 Origin of the EL5 level is not fully established, nevertheless it is frequently accepted that it is a complex point defect involving gallium vacancy (V Ga ) together with, e.g., Si Ga 44 or As i . 43 It is also known that high Si doping leads to a generation of gallium vacancies or V Ga -related complexes. 31 Fushimi et al 30 showed by comparing transport and SIMS measurements that these defects, suppressing free electron concentration, appear in concentration at least few percent of the Si concentration already in the range of 10 24 m Ϫ3 of silicon doping.…”
Section: Resultsmentioning
confidence: 99%
“…Its properties are identical to that of the native defect EL5 in GaAs (Reddy, 1996). Its atomic structure was discussed in many publications, where the common result indicated that EL5 is a complex defect free from impurities and dominated by As interstitials, such V Ga -As i or As Ga -V Ga (Deenapanray et al, 2000;Yakimova et al, 1993). The second new defect is a hole trap (HP1) at approximately an average activation energy 0.11 eV above the VBM of GaAsN.…”
Section: Effect Of H Implantation On Lattice Defects In Gaasnmentioning
confidence: 75%